2011
DOI: 10.1007/s00234-011-0875-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of neuromyelitis optica (NMO) spectrum disorders: is MRI obsolete?

Abstract: The NMO spectrum of diseases are among an increasing number of neurological conditions defined by serological tests. However, despite improved immunoassay techniques, MRI of the brain and spinal cord continues to be among the first-line investigations in these patients, providing valuable diagnostic information that will help guide patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 30 publications
5
56
1
2
Order By: Relevance
“…As a substantial portion of NMO patients in clinic have brain involvement, further study should identify which imaging features are truly characteristic of NMO, and can be included in the diagnostic workup. Conversely, our clinical experience and another study [7] also support that presence of typical MS lesions cannot exclude the clinical diagnosis of NMO, particularly in the Asian populations. A Japanese study showed that brain MRI lesions (including typical ovoid periventricular lesions) were indistinguishable between MS and NMO [8].…”
Section: Introductionsupporting
confidence: 53%
“…As a substantial portion of NMO patients in clinic have brain involvement, further study should identify which imaging features are truly characteristic of NMO, and can be included in the diagnostic workup. Conversely, our clinical experience and another study [7] also support that presence of typical MS lesions cannot exclude the clinical diagnosis of NMO, particularly in the Asian populations. A Japanese study showed that brain MRI lesions (including typical ovoid periventricular lesions) were indistinguishable between MS and NMO [8].…”
Section: Introductionsupporting
confidence: 53%
“…These longitudinally extensive spinal cord lesions (LESCLs) are commoner in AQP4 positive patients than those who are negative for the antibody and patient may show short segment T2 hyper-intense lesions on imaging. Delayed imaging after the beginning of symptoms may also result in short segment lesions [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The optic nerves may show bilateral involvement, altered signal intensity with posterior extension into the optic chiasma and contrast enhancement [12,13]. In the acute phase, pulse dose methyl-prednisolone therapy is the treatment of choice followed by tapering dose of oral steroid for 2-6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, we have observed short segments of gadolinium enhancement within pre-existing T2 LESCLs during acute spinal relapse (Fig 1A, -B). Additionally, short-segment T2-hyperintense lesions are described in NMO 20 and should not necessarily deter one from the diagnosis, particularly in the presence of other typical neuroimaging findings. While cord pathology in NMO is traditionally associated with a severe clinical phenotype, including the need for ventilatory support in association with high cervical lesions, excellent clinical and radiologic recovery may be seen in some patients.…”
Section: Typical Spinal Cord Imaging Featuresmentioning
confidence: 98%